Netralitas Konten Berita Online (Analisis Framing: Berita Reuni Alumni 212 di detik.com) - Wardani, Ajeng Dwi; Indrayani, Heni (Interaksi: Jurnal Ilmu Komunikasi, 2018)
Religion issue recently gets much attention in Indonesian media coverage. A Rally named ‘212 alumni reunion’ to celebrate the anniversary of a previous rally that demanded the prosecution of then Jakarta Governor Basuki ‘Ahok’ Tjahaja Purnama after he was accused of blasphemy became national-wide coverage of national media. By using the framing analysis method, this article tries to illustrate how an online media, detik.com, have or have not applied journalism principal in coveting that religious issue. The result of the study shows that detik.com have done media function because it has applied media principle of neutrality. This research did not find any subjective opinion and political interest in the text. Besides that, detik.com was more focusing on the using of ‘what’ element of news as well as the ‘who’ element for describing the issue more objectively.